Hoax News and Future Threats: A Study of the Constitution, Pancasila, and the Law - Aisyah, Siti; Dika, Muhammad Fathan Zahran; Yasmin, Afra; Hanifah, Tarissa Putri; Pradana, Floribertus Bujana Adi (Indonesian Journal of Pancasila and Global Constitutionalism, 2022)
The rise of fake news (hoax) circulating in the community is a serious threat to the Indonesian nation, because it can divide the unity of Indonesia. Indonesia, which is a multi-cultural country consisting of various religions, ethnicities, races, and ethnicities, is vulnerable to conflicts between community groups. Fake news is news that contains information that is not in accordance with the actual situation. Fake news aims to deceive, cause hatred, or hostility to certain individuals or groups of people based on religion, race, and between groups. This paper explains how fake news or hoaxes can break Indonesian unity. How is fake news in the perspective of criminology to find out the motives and goals of the perpetrators of spreading fake news, fake news in the perspective of Pancasila, as well as the efforts that can be made by the community and government to prevent and overcome the spread of fake news. The thing to do to prevent fake news is to sort out the news in order to prevent believing in fake news (hoax), by not only reading the news title, but also paying attention to the URL address of the site, and checking the facts, whether the content of the news is credible and sourced from official institution.